The spillover effects of gender quotas on dishonesty - Valeria Maggian; Natalia Montinari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
We experimentally test for spillover effects of gender quotas on subsequent unrelated, unethical behavior. We find that introducing quotas has no systematic effect on unethical behavior for both genders. High performing, competitive females are more likely to display unethical behavior than their male counterparts.
Keywords: D03; C91; J24; 330; Affirmative action; spillover effects; unethical behavior; competition; laboratory experiments